EVALUATION OF THE EFFECTIVENESS OF METHODS OF DETECTING WEAKNESSES AND NETWORK ATTACKS - Ibrokhimov A. R.; Haydarov E. D. (Journals Park Publishing, 2023)
The article contains the evaluation of the effectiveness of the methods of detecting vulnerabilities and network attacks, the recommendations proposed by the Cyber Security Center to increase the effectiveness of the detection of vulnerabilities and network attacks and the provision of information security, the results of the three-step testing method for detecting vulnerabilities on servers, the results of the evaluation of the effectiveness of the VITE method of detecting network attacks given.
Keywords: network attacks, vulnerability, website, OWASP, injection vulnerabilities, business logic vulnerabilities, session management vulnerabilities, web server vulnerability detection software, web server data protection software from network attacks, VITE.